A CRITICAL DISCOURSE ANALYSIS OF THE LANGUAGE OF WEBINARS: POLITICS BUILDING TASK - MOHAMAD , MARIA SALIM; AL-RUBAI’I, ALYA M.H.AHMED (Journal of Duhok University, 2020)
ABSTRACT. This study aims at analyzing how through language use, power relations are built in webinars. Recently, webinars have become very popular as effective instructional tools in education. They are one type of multi-synchronous system used for online education. This study follows a qualitative methodology. Five webinars from Edweb.net meant for personalized professional learning are analyzed critically, and the texts are described and explained using James Paul Gee’s (2014a) approach and method of critical discourse analysis. According to the scope of this study, only the politics building task, among seven building tasks and the social language tool, the figured world tool, and the situated meaning tool are used as tools of inquiry for data analysis. This study clarifies how speakers give or take social goods from persons, institutions or things based on some ideological principles in certain social groups. It explains that speakers do not only say things through language but also do things and be things. It has been found out that teachers have the power of maintaining discipline and are authoritative in classroom management while students are given less power regarding discipline. Additionally, technology in the 21st century is seen as an innovative powerful source in education as in other fields too.